FAKTOR-FAKTOR PENGHAMBAT DALAM PENYELESAIAN SKRIPSI MAHASISWA DI JURUSAN KESEJAHTERAAN KELUARGA - Julita, Julita; Elida, Elida; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The research was conducted with the aim to describe the restricted factorsin the completion of an undergraduate thesis in the Department of that includesinternal and external factors. Types of research are qualitative and descriptive mixmethods (Mixed Method). This research was conducted in the Department ofhome economic in April. Sources of quantitative data obtained fromundergraduate students of culinary school in 2009-2011 who are taking thecourses thesis as many as 42 people, sources of qualitative data obtained from theDepartment of home economic undergraduate students in culinary school in 2009-2011 who are taking the undergraduate thesis. Quantitative data collectiontechniques with questionnaire, qualitative data with observation, interview anddocumentation. The result showed that, in general the barriers of college studentsin the completion of a thesis in terms of internal factors (motivation) is alreadyquite well with percentage score of 45,23%. But the barriers of college students inthe completion of a thesis review of external factors (look for material or title ofthe thesis, literature search and the problem when consulting the advisorundergraduate thesis) still constrained.Keyword : Restricting Factors in the completion, of an undergraduate thesis